2017
DOI: 10.3389/fnhum.2017.00420
|View full text |Cite|
|
Sign up to set email alerts
|

Static and Dynamic Measures of Human Brain Connectivity Predict Complementary Aspects of Human Cognitive Performance

Abstract: In cognitive network neuroscience, the connectivity and community structure of the brain network is related to measures of cognitive performance, like attention and memory. Research in this emerging discipline has largely focused on two measures of connectivity—modularity and flexibility—which, for the most part, have been examined in isolation. The current project investigates the relationship between these two measures of connectivity and how they make separable contribution to predicting individual differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…While modularity measures the depth of the attractor states, flexibility measures the frequency of the brain transitioning between states. Deeper states are more stable and will be more resistant to change, and so the regions in these states will have lower flexibility and vice versa (Ramos-Nuñez et al, 2017). We found that in the TD group, the mean whole-brain flexibility shows a significant ( p = 0.001) correlation ( r = −0.35) with modularity (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While modularity measures the depth of the attractor states, flexibility measures the frequency of the brain transitioning between states. Deeper states are more stable and will be more resistant to change, and so the regions in these states will have lower flexibility and vice versa (Ramos-Nuñez et al, 2017). We found that in the TD group, the mean whole-brain flexibility shows a significant ( p = 0.001) correlation ( r = −0.35) with modularity (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Flexibility also has age-based variation (Schlesinger et al, 2017). Recent work has established that there is a significant negative correlation between flexibility and modularity using task-based fMRI studies (Ramos-Nuñez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, global flexibility was highly negatively correlated with modularity, suggesting that more segregated networks are also more resistant to change, and thus exhibit lower variability across a certain time span (Harlalka, Bapi, Vinod, & Roy, 2019; Meunier, Lambiotte, & Bullmore, 2010; Ramos‐Nuñez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a network, flexibility is the number of times that each node changes allegiance, normalized by the total possible number of changes during scan time windows. It is a basic parameter used to understand how network reconfiguration occurs over time and measures the changes in the adherence of one community to another over time 15,17,135 . We sought to understand the flexible nature of the neural processes involved in creative cognition by using a network reconfiguration methodology to determine changes in the communities in brain networks and examine the consistency between static and temporal brain networks.…”
Section: Discussionmentioning
confidence: 99%